Assessment of resistance definitions used for blast analysis of unreinforced masonry walls. Issue 1 (March 2017) - Gagnet, Eric M; Hoemann, John M; Davidson, James S
Over recent decades, three distinct methods have evolved that are currently being used to generate resistance functions for single-degree-of-freedom analyses of unreinforced masonry walls subjected to blast loading. The degree of differences in these resistance definitions depends on whether the wall is assumed to be simply supported or whether compression arching forces result from rotation restraint at the supports. The first method originated in the late 1960s as a result of both experimental and analytical research sponsored by the US Department of Defense. That method, referred to as the Wiehle method, is the basis of Unified Facilities Criteria 3-340-02 and other derived analytical software such as the Wall Analysis Code developed by the US Army Corps of Engineers, Engineer Research and Development Center. The second method is based on elastic mechanics and an assumed linear decay function that follows and is the basis of the widely used Single-Degree-of-Freedom Blast Effects Design Spreadsheets software distributed by the US Army Corps of Engineers, Protective Design Center. The third method is largely based on concrete and masonry behavioral theories developed by Paulay and Priestly in the early 1990s. This article systematically compares the resistance methodologies for arching and non-arching scenarios, demonstrates the implications by plugging the disparate resistance functions into blast load single-degree-of-freedom models, compares the analytical results to full-scale blast test results, and offers conclusions about the accuracy and efficacies of each method.